Sistem Informasi Toko X Menggunakan Metode Analytical Hierarchy Process Untuk Rekomendasi Supplier - Merpanto Kaneko; Radiant Victor Imbar (Maranatha University Press, 2017)
X is a trading companies. Technological developments now make the information system needed by each company in order to compete with other trading companies. Choose the best supplier is not easy, therefore x store need information systems to help the owner to make desicion for procure material using Decision Support System using Analytical Hierarchy Process method for selecting the best suppliers and also implement information system of sales, purchasing, and accounting. Analytical Hierarchy Process is used to determine the best suppliers in terms of quality, delivery time, and price. By doing so, administrators can easily manage data sales, purchasing, accounting, and supplier selection.